Automatic identification by C-13 NMR of substituent groups bonded in natural product skeletons - Ferreira, MJP; Oliveira, F. C.; Alvarenga, SAV; Macari, PAT; Rodrigues, G. V.; Emerenciano, V. P. (Elsevier B.V., 2002)
The aim of this paper is to present a procedure that utilizes C-13 NMR for identification of substituent groups which are bonded to carbon skeletons of natural products. For so much was developed a new version of the program (MACRONO), that presents a database with 161 substituent types found in the most varied terpenoids. This new version was widely tested in the identification of the substituents of 60 compounds that, after removal of the signals that did not belong to the carbon skeleton, served to test the prediction of skeletons by using other programs of the expert system (SISTEMAT). (C) 2002 Elsevier B.V. Ltd. All rights reserved.
Keywords: terpenoids; natural products; C-13 NMR; substituent elucidation; expert system